1-Butyl-3-methylimidazolium tetrafluoroborate as suitable solvent for BF3: the case of alkyne hydration. Chemistry vs electrochemistry - David, Marta; Galli, Elisa; Brown, Richard C. D.; Feroci, Marta; Vetica, Fabrizio; Bortolami, Martina (Beilstein Journal of Organic Chemistry, 2023)
In order to replace the expensive metal/ligand catalysts and classic toxic and volatile solvents, commonly used for the hydration of alkynes, the hydration reaction of alkynes was studied in the ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate (BMIm-BF4) adding boron trifluoride diethyl etherate (BF3·Et2O) as catalyst. Different ionic liquids were used, varying the cation or the anion, in order to identify the best one, in terms of both efficiency and reduced costs. The developed method was efficaciously applied to different alkynes, achieving the desired hydration products with good yields. The results obtained using a conventional approach (i.e., adding BF3·Et2O) were compared with those achieved using BF3 electrogenerated in BMIm-BF4, demonstrating the possibility of obtaining the products of alkyne hydration with analogous or improved yields, using less hazardous precursors to generate the reactive species in situ. In particular, for terminal arylalkynes, the electrochemical route proved to be advantageous, yielding preferentially the hydration products vs the aldol condensation products. Importantly, the ability to recycle the ionic liquid in subsequent reactions was successfully demonstrated.
Keywords: alkyne hydration; boron trifluoride; electrochemical synthesis; ionic liquids